2011
DOI: 10.5511/plantbiotechnology.11.0121a
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis chimeric TCP3 repressor produces novel floral traits in Torenia fournieri and Chrysanthemum morifolium

Abstract: Shape and color are the most important characteristics of ornamental flowers, and the generation of the novel phenotypes has been pursued in the breeding. Distinct floral morphology such as fringed petals and double flowers has been selected preferentially in the breeding of horticultural crops from wild species.Transcription factors control the expression of multiple genes and act as the master regulator of various phenotypes. Most of the floral morphological changes in Arabidopsis reported until date are att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…As a consequence, these two transcription genes were chosen to provide suggestive and contrasting results. All the flowers transformed with chimeric TCP-related repressors exhibited similar morphological changes, such as serrated margins of the vegetative tissues and unique petal color patterns (Gion et al 2011;Narumi et al 2011;Tanaka et al 2011aTanaka et al , 2011b. In addition, we confirmed that repressive activity occurs only when the chimeric repressor has an intact repression domain, using diploid torenia and hexaploid chrysanthemum .…”
Section: Tcp3 and Agsupporting
confidence: 60%
“…As a consequence, these two transcription genes were chosen to provide suggestive and contrasting results. All the flowers transformed with chimeric TCP-related repressors exhibited similar morphological changes, such as serrated margins of the vegetative tissues and unique petal color patterns (Gion et al 2011;Narumi et al 2011;Tanaka et al 2011aTanaka et al , 2011b. In addition, we confirmed that repressive activity occurs only when the chimeric repressor has an intact repression domain, using diploid torenia and hexaploid chrysanthemum .…”
Section: Tcp3 and Agsupporting
confidence: 60%
“…Representative results are summarized in Table 2. The TEOSINTE BRANCHED1, CYCLOIDEA and PCF (TCP) TFs induced the expected phenotypes in most examined species even when the Arabidopsis gene was employed (Table 2) (Gion et al 2011;Narumi et al 2011;Tanaka et al 2011), while the Arabidopsis MADS box TFs, such as AGAMOUS (AG) and APETALA3 (AP3), did not induce the expected phenotypes in plants other than Arabidopsis (Table 2). However, as shown for morning glory, when orthologs of the MADS box TFs from each species was employed, the expected phenotypes were induced (Table 2) (Sage-Ono et al 2011).…”
Section: Browsing Constructsmentioning
confidence: 99%
“…In addition, SRDX is effective for many ornamental crops, such as Torenia, rose, gentian, lisianthus, cyclamen, chrysanthemum, and morning glory (Mitsuda et al 2008, Mitsuda et al 2011a. Because this system functions dominantly, the chimeric repressors even worked in higher polyploidy plants, such as the hexaploid chrysanthemum (Mitsuda et al 2011a, Narumi et al 2011. It is noteworthy that chimeric repressors constructed with Arabidopsis TFs frequently worked in other ornamental crops for the functional analysis of TFs and the development of novel floral traits without any further modification (Narumi et al 2011, Shikata et al 2011, Gion et al 2011.…”
Section: Development and Application Of Cres-t In Ornamental Cropsmentioning
confidence: 99%
“…Because this system functions dominantly, the chimeric repressors even worked in higher polyploidy plants, such as the hexaploid chrysanthemum (Mitsuda et al 2011a, Narumi et al 2011. It is noteworthy that chimeric repressors constructed with Arabidopsis TFs frequently worked in other ornamental crops for the functional analysis of TFs and the development of novel floral traits without any further modification (Narumi et al 2011, Shikata et al 2011, Gion et al 2011. Information regarding the floral phenotypes generated in the CRES-T project is available on the FioreDB website: Database for Flower Bio-engineering by CRES-T (Mitsuda et al 2011a; http://www.cres-t.org/fiore/public_db/index.…”
Section: Development and Application Of Cres-t In Ornamental Cropsmentioning
confidence: 99%